A mold-induced color-changing epoxy resin material and its preparation method and application

By introducing force-discolored epoxy resin materials into epoxy resin molds, the problem of lack of damage warning mechanism in traditional epoxy resin molds is solved, early damage detection is achieved and the mechanical properties of the material is significantly improved.

CN118791836BActive Publication Date: 2025-04-22BEIJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411090950.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-04-22
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Traditional epoxy resin molds lack effective damage warning mechanism when facing accidental impact or overload operations, resulting in tiny cracks or damage that are difficult to directly observe with the naked eye, affecting the production process and product quality.

Method used

Develop a mold-forced colored epoxy resin material. By introducing force-colored epoxy resin, polyamide curing agent, accelerator and aqueous filler, the material can quickly feedback through color changes when damaged and detect damage in the early stage.

Benefits of technology

It significantly improves the force color rendering effect and fluorescence opening response of the mold material, enhances the damage visualization ability, can promptly warn operators or automatic monitoring systems, and improves the bending strength and hardness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791836B_ABST
    Figure CN118791836B_ABST
Patent Text Reader

Abstract

The present invention relates to a mechanochromic epoxy resin material for molds and a preparation method and application thereof, and belongs to the technical field of epoxy resin materials. The mechanochromic epoxy resin material for molds comprises a mechanochromic epoxy resin, a polyamide curing agent, an accelerator and an aqueous filler; the mechanochromic epoxy resin is prepared by: mixing rhodamine and ethylenediamine with anhydrous ethanol and then refluxing, filtering, washing and drying; mixing the obtained modified rhodamine with epoxy resin and treating at 130-180°C for 2-4h; mixing the obtained rhodamine-modified epoxy resin and curing agent, then adding nano-alumina and mixing, and then stirring at 60-100°C to obtain a mechanochromic epoxy resin with a viscosity of 40000-45000cps. The present invention can significantly improve the stress color development effect of the mold material and enhance the fluorescence on-response, is suitable for damage detection and / or damage warning, and can improve the bending strength and hardness of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy resin materials, and in particular relates to a mold force-induced color-changing epoxy resin material and a preparation method and application thereof. Background Art

[0002] Epoxy resins, due to their excellent mechanical properties, adhesion and chemical stability, have been widely used in a variety of industrial fields, including precision mold manufacturing, high-performance coatings, aerospace components and electronic packaging. Although epoxy resins excel in many aspects, their inherent brittleness and lack of effective damage warning mechanisms when facing unexpected impacts or overload operations limit their use in high-risk application scenarios.

[0003] In industrial production and daily applications, molds are often subject to repeated mechanical stress and environmental challenges, such as high temperature and chemical corrosion. Traditional epoxy resin molds are difficult to detect in the early stages of damage, and when visible damage occurs, it usually causes irreversible damage to the production process or product quality. Therefore, it is very necessary to develop an epoxy resin mold with self-indicating damage, which can provide obvious visual or other perceptual signals in the early stages of damage, thereby allowing timely maintenance or replacement, greatly improving the operational safety and economic efficiency of the equipment.

[0004] In addition, with the advancement of technology and the improvement of industrial standards, the requirements for molds are also constantly upgrading. High-performance molds not only need to have excellent mechanical and thermal properties, but also should have high reliability and predictability. In the fields of aerospace, high-speed transportation and precision electronics, the damage warning function of epoxy resin molds significantly improves the safety and stability of the entire system, but this is difficult to achieve using traditional materials.

[0005] Therefore, it is very urgent to develop a new type of mold-induced color-changing epoxy resin material, which can quickly respond through color changes when damaged, so as to achieve early detection of damage. The epoxy resin mold made of this material will also fill the gap in safety warning of traditional epoxy resin molds.

[0006] In summary, it is very necessary to provide a mold force-induced color-changing epoxy resin material and its preparation method and application. Summary of the invention

[0007] In order to solve one or more technical problems existing in the prior art, the present invention provides a force-induced color-changing epoxy resin material for molds and a preparation method and application thereof. The present invention can significantly improve the force-induced color-changing effect of the mold material and strengthen the fluorescence on-response, is suitable for damage detection and / or damage warning, and can improve the bending strength and hardness of the material.

[0008] In a first aspect, the present invention provides a mechanochromic epoxy resin material for a mold, wherein the mechanochromic epoxy resin material for a mold comprises a mechanochromic epoxy resin, a polyamide curing agent, an accelerator and an aqueous filler; the preparation of the mechanochromic epoxy resin comprises the following steps:

[0009] (1) mixing rhodamine 6G and ethylenediamine uniformly with anhydrous ethanol and subjecting the mixture to a reflux reaction, followed by filtering, washing and drying to obtain modified rhodamine;

[0010] (2) uniformly mixing the modified rhodamine and the epoxy resin and treating at 130 to 180° C. for 2 to 4 hours to obtain a rhodamine-modified epoxy resin;

[0011] (3) The rhodamine-modified epoxy resin and the curing agent are mixed uniformly to obtain a first mixture, and then nano-alumina is added to the first mixture and mixed uniformly to obtain a second mixture, and then the second mixture is stirred at 60 to 100° C. to obtain a mechanochromic epoxy resin with a viscosity of 40,000 to 45,000 cps.

[0012] Preferably, the molar ratio of the rhodamine 6G to the ethylenediamine is 1:(3.5-4.5); the mass ratio of the anhydrous ethanol to the rhodamine 6G is (10-15):1; and / or the temperature of the reflux reaction is 70-90°C, and the time of the reflux reaction is 18-30h.

[0013] Preferably, the epoxy resin is bisphenol A epoxy resin; and / or the mass ratio of the modified rhodamine to the epoxy resin is 1:(15-25).

[0014] Preferably, in step (3): the curing agent is an anhydride curing agent and / or an amine curing agent; the mass ratio of the rhodamine-modified epoxy resin to the curing agent is 100:(20-40):(1-5); and / or the mass ratio of the first mixture to the nano-alumina is 100:(20-70).

[0015] Preferably, the stirring speed of the stirring process is 100 to 400 r / min.

[0016] Preferably, the mechanochromic epoxy resin material for the mold also contains bisphenol F epoxy resin, and the mass ratio of the mechanochromic epoxy resin to the bisphenol F epoxy resin is 10:(2-8); the mass ratio of the mechanochromic epoxy resin, the polyamide curing agent, the accelerator and the aqueous phase filler is 10:(3-8):(0.5-1.5):(50-80); and / or the aqueous phase filler contains hydrophilic fumed silica, precipitated white carbon black, nano titanium dioxide and water in a mass ratio of (15-25):(5-15):(5-15):(20-30).

[0017] Preferably, the polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636; and / or the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

[0018] In a second aspect, the present invention provides a method for preparing the mold force-induced color-changing epoxy resin material according to the first aspect of the present invention, the method comprising the following steps:

[0019] (a) mixing hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide with water to obtain an aqueous phase filler;

[0020] (b) The mechanochromic epoxy resin, the polyamide curing agent and the accelerator are mixed uniformly, and then the aqueous phase filler is added and mixed uniformly to obtain a mechanochromic epoxy resin material for a mold.

[0021] Preferably, in step (b), bisphenol F epoxy resin is also added.

[0022] The third aspect of the present invention provides the use of the mold-induced chromic epoxy resin material described in the first aspect of the present invention or the mold-induced chromic epoxy resin material prepared by the preparation method described in the second aspect of the present invention in the preparation of epoxy resin molds for damage detection and / or damage warning.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] (1) The present invention provides a mechanochromic epoxy resin material for damage detection and / or damage warning. The present invention realizes an intuitive response to mechanical stress by introducing a mechanochromic epoxy resin, enhances the damage visualization capability, and enables the damage to be directly visualized through color changes at an early stage, thereby timely alerting the operator or the automatic monitoring system, thereby solving the problem that the tiny cracks or damage of traditional epoxy resin molds are often difficult to directly observe with the naked eye in practical applications, especially when subjected to repeated loads or exposed to harsh environments. Under the premise of not affecting the mechanical properties and chemical stability of the epoxy resin itself, the present invention optimizes the combination of rhodamine and epoxy resin so that the introduced mechanochromic epoxy resin can achieve a highly reversible color change effect. The introduced mechanochromic epoxy resin can still maintain good color change characteristics after repeated stress, thereby ensuring the practicality of the prepared epoxy resin mold in long-term use.

[0025] (2) The mechanochromic epoxy resin material for molds of the present invention comprises a composite material of epoxy resin modified with rhodamine mechanochromic sensitive groups and nano-alumina, and is a mechanical force responsive composite material with more obvious color and fluorescence response. The combination of rhodamine mechanochromic sensitive group modification and the addition of nano-alumina can significantly improve the force color development effect and enhance the fluorescence on-response without sacrificing its mechanical properties, which not only improves the sensitivity of the epoxy resin mold to small stress changes, but also can more accurately evaluate the degree of damage and potential risks through the range and depth of color change, thereby improving The accuracy and sensitivity of loss detection are improved, while conventional epoxy resins only mixed with rhodamine often have problems of delayed response or insufficient sensitivity; the mechanochromic epoxy resin in the present invention not only improves the color development effect of the rhodamine-modified epoxy resin after being subjected to force, but also maintains excellent mechanical properties, thereby ensuring the stability of the mechanochromic epoxy resin material for the mold in the present invention under extreme conditions, and can avoid the influence of environmental factors on its color-changing performance and mechanical strength; the present invention can significantly improve the safety, reliability and maintenance efficiency of the prepared epoxy resin mold in industrial applications, bringing substantial benefits to users and manufacturers.

[0026] (3) The force-induced color-changing epoxy resin material for molds in the present invention contains a force-induced color-changing epoxy resin compounded with rhodamine-modified epoxy resin and nano-alumina. The present invention finds that the two do not act alone. Compared with conventional epoxy resin, rhodamine-modified epoxy resin can improve the dispersion uniformity of nano-alumina and effectively prevent the sedimentation of nano-alumina. The addition of nano-alumina can effectively improve the force-induced color-changing effect of rhodamine-modified epoxy resin, which is the first discovery of the present invention. Although the prior art has filled alumina into epoxy resin to improve the thermal conductivity, dielectric constant and weather resistance of epoxy resin, it has never been reported that nano-alumina can promote the force-induced color change and fluorescence on-response of rhodamine-modified epoxy resin.

[0027] (4) In order to further solve the problem of obvious sedimentation of alumina particles in the mechanochromic epoxy resin material, the present invention, in the process of preparing the mechanochromic epoxy resin, obtains a mechanochromic epoxy resin with a viscosity controlled at 40,000 to 45,000 cps by stirring the second mixed material, thereby optimizing the subsequent curing process of the mechanochromic epoxy resin. The present invention finds that by controlling the viscosity of the mechanochromic epoxy resin at 40,000 to 45,000 cps, the viscous resistance of the nano-alumina particles to sedimentation is effectively increased, and the mechanochromic epoxy resin is not changed. On the basis of the mechanochromic epoxy resin component, after this stirring treatment pre-crosslinking operation, the interfacial bonding degree between the rhodamine modified epoxy resin and the nano-alumina is significantly enhanced, and the dispersion and uniformity of the nano-alumina in the rhodamine modified epoxy resin are significantly improved, which can effectively solve the problem of the sedimentation of the nano-alumina filler. Since a mechanochromic epoxy resin with a lower sedimentation rate and a more uniform material is prepared, the uniformity of the performance of the mechanochromic epoxy resin material for the final mold is effectively guaranteed, which is also beneficial to improve its mechanochromic properties and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a preparation flow chart of some specific embodiments of the present invention;

[0029] Figure 2 It is a fluorescence spectrum curve diagram of the mold force-induced color-changing epoxy resin material cured sample obtained in Example 1 of the present invention before and after compression deformation; in the figure, (a) is the fluorescence spectrum curve diagram before compression treatment; (b) is the fluorescence spectrum curve diagram after 20MPa compression treatment. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In a first aspect, the present invention provides a mechanochromic epoxy resin material for a mold (also referred to as a mold epoxy resin material), wherein the mechanochromic epoxy resin material for a mold comprises a mechanochromic epoxy resin, a polyamide curing agent, an accelerator, and an aqueous filler; the preparation of the mechanochromic epoxy resin comprises the following steps:

[0032] (1) mixing rhodamine 6G and ethylenediamine uniformly with anhydrous ethanol, performing a reflux reaction, and then filtering, washing and drying to obtain modified rhodamine; in the present invention, the washing is performed by, for example, anhydrous ethanol, and the drying is performed by, for example, drying at 50 to 80° C. for 2 to 5 hours;

[0033] (2) After the modified rhodamine and epoxy resin are uniformly mixed, they are treated at 130-180°C (for example, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C) for 2-4h (for example, 2, 2.5, 3, 3.5 or 4h) to obtain a rhodamine-modified epoxy resin; in the present invention, after the rhodamine-modified epoxy resin material formed by introducing the rhodamine 6G modified by ethylenediamine into the epoxy resin is subjected to force, the force can directly act on the chemical bond from both ends of the weak bond (CN bond) along the polymer chain, so that the rhodamine molecule is transformed from a closed ring form with almost no fluorescence to an open ring form with colored fluorescence, and has a mechanochromic effect; through the unique design of the rhodamine-modified epoxy resin, the present invention can realize the instant visual response of the mold mechanochromic epoxy resin material when it is subjected to mechanical force. This color change can intuitively display the damage location and degree, which is a function that the traditional epoxy resin only mixed with rhodamine does not have, and can significantly improve the early warning efficiency;

[0034] (3) Mixing the rhodamine modified epoxy resin and the curing agent evenly to obtain a first mixed material, and then adding nano-alumina (nano-Al 2 O 3 ) and mix them evenly to obtain a second mixture, and then stir the second mixture at 60-100°C (for example, 60°C, 70°C, 80°C, 90°C or 100°C) to obtain a mechanochromic epoxy resin with a viscosity of 40,000-45,000 cps; the present invention does not impose any specific restriction on the time for the stirring treatment, as long as a pre-crosslinked material with a viscosity of 40,000-45,000 cps is obtained; the present invention does not impose any specific restriction on the stirring speed of the stirring treatment, for example, it can be 100-400 r / min; in the present invention, the nano alumina is nano spherical alumina, and the present invention does not impose any specific restriction on the particle size of the nano alumina, for example, it can be 80-100 nm.

[0035] The present invention provides a mechanochromic epoxy resin material for a mold for damage detection and / or damage warning. The present invention realizes an intuitive response to mechanical stress and enhances the damage visualization capability by introducing a mechanochromic epoxy resin, so that the damage can be directly visualized through color change at an early stage, thereby timely alerting the operator or the automatic monitoring system, and solving the problem that the tiny cracks or damages of the traditional epoxy resin mold are often difficult to be directly observed by the naked eye in practical applications, especially when subjected to repeated loads or exposed to harsh environments. Under the premise of not affecting the mechanical properties and chemical stability of the epoxy resin itself, the present invention optimizes the combination mode of rhodamine and epoxy resin so that the introduced mechanochromic epoxy resin can achieve a highly reversible color change effect. The introduced mechanochromic epoxy resin can still maintain good color change characteristics after repeated stress, and can ensure the practicality of the prepared epoxy resin mold in long-term use.

[0036] The mechanochromic epoxy resin material for molds of the present invention comprises a composite material of epoxy resin modified with rhodamine mechanochromic force-sensitive groups and nano-alumina, and is a mechanical force response composite material with more obvious color and fluorescence response. The mechanochromic effect of stress and the fluorescence on response can be significantly improved without sacrificing its mechanical properties by combining the modification of rhodamine force-sensitive groups with the addition of nano-alumina. The sensitivity of epoxy resin molds to small stress changes can also be more accurately evaluated through the range and depth of color changes. The damage degree and potential risk are improved. The accuracy and sensitivity of loss detection are improved, while conventional epoxy resins only mixed with rhodamine often have problems of delayed response or insufficient sensitivity; the mechanochromic epoxy resin in the present invention not only improves the color development effect of the rhodamine-modified epoxy resin after being subjected to force, but also maintains excellent mechanical properties, thereby ensuring the stability of the mechanochromic epoxy resin material for the mold in the present invention under extreme conditions, and can avoid the influence of environmental factors on its color-changing performance and mechanical strength; the present invention can significantly improve the safety, reliability and maintenance efficiency of the prepared epoxy resin mold in industrial applications, bringing substantial benefits to users and manufacturers.

[0037] The force-induced color-changing epoxy resin material for molds in the present invention contains a force-induced color-changing epoxy resin compounded with rhodamine-modified epoxy resin and nano-alumina. The present invention finds that the two do not act alone. Compared with conventional epoxy resin, rhodamine-modified epoxy resin can improve the dispersion uniformity of nano-alumina and effectively prevent the sedimentation of nano-alumina. The addition of nano-alumina can control the local environment of rhodamine-modified epoxy resin, further enhance its reaction characteristics at the microscopic level, and effectively improve the force-induced color-changing effect of rhodamine-modified epoxy resin, making the color-changing reaction more sensitive and accurate. This is discovered for the first time in the present invention. The possible reason is that nano-alumina has a large specific surface area and high surface energy, and can produce a strong interface interaction with the rhodamine-modified epoxy resin matrix. This interface force helps to improve the mechanical properties of the material. , thereby enhancing the color development effect under stress; Rhodamine-modified epoxy resin can improve the uniformity of dispersion of nano-alumina in the resin matrix, avoid the agglomeration and sedimentation of nanoparticles, and the evenly dispersed nanoparticles can form a more uniform stress distribution, thereby showing a more obvious color development effect under stress, and the addition of nano-alumina can improve the toughness and impact resistance of the material. This toughening effect can produce more microcracks and plastic deformation under stress, so that the rhodamine-modified epoxy resin has a more obvious response in these microcracks or deformation areas, which is also conducive to enhancing the color development effect; although there is a method of filling alumina into epoxy resin to improve the thermal conductivity, dielectric constant and weather resistance of epoxy resin in the prior art, it has never been reported that nano-alumina can promote the stress color change and fluorescence on-response of rhodamine-modified epoxy resin.

[0038] After curing, the existing epoxy resin filled with alumina has obvious sedimentation of alumina particles in the material, and as the alumina content increases, the cross-sectional stratification of the epoxy resin material is usually more serious, which will cause differences in the performance of each part of the material, resulting in uneven strength distribution of the material, reduced durability, unstable mechanical properties and greatly increased production costs. In order to solve this problem, it is necessary to study a method to make the nano-alumina filler in rhodamine-modified epoxy resin evenly distributed. In order to solve the problem of obvious sedimentation of alumina particles in rhodamine modified epoxy resin materials, the present invention comprehensively considers the dispersion uniformity of mechanochromic epoxy resin and aqueous filler, etc., and optimizes the subsequent curing process of mechanochromic epoxy resin as much as possible by stirring the second mixed material during the preparation of the mechanochromic epoxy resin. The present invention finds that by controlling the viscosity of the mechanochromic epoxy resin to 40,000-45,000 cps, on the one hand, the viscous resistance of the sedimentation of nano-alumina particles can be increased. After this stirring treatment pre-crosslinking operation, the interface bonding degree between the rhodamine modified epoxy resin and the nano-alumina is enhanced, and the dispersibility and uniformity of the nano-alumina in the rhodamine modified epoxy resin are improved, which can effectively solve the problem of sedimentation of the nano-alumina filler. Since a mechanochromic epoxy resin with a lower sedimentation rate and a more uniform material is prepared, the uniformity of the performance of the mechanochromic epoxy resin material for the mold prepared in the end is effectively guaranteed, which is also conducive to improving its mechanochromic characteristics and mechanical properties.

[0039] According to some preferred embodiments, the molar ratio of the rhodamine 6G to the ethylenediamine is 1:(3.5-4.5) (e.g., 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4 or 1:4.5); the mass ratio of the anhydrous ethanol to the rhodamine 6G is (10-15):1 (e.g., 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1); and / or the temperature of the reflux reaction is 70-90°C (e.g., 70°C, 75°C, 80°C, 85°C or 90°C), and the time of the reflux reaction is 18-30h (e.g., 18, 20, 22, 24, 26, 28 or 30h).

[0040] According to some specific embodiments, step (1) is: in a round-bottom flask equipped with a reflux condenser, rhodamine 6G is dissolved in anhydrous ethanol, and then an excess of ethylenediamine is added and mixed evenly, and then refluxed for 24 hours under an argon atmosphere at 80°C; the obtained substance is filtered, washed three times with anhydrous ethanol, and then dried in an oven at 60°C for 3 hours to obtain a dry powder product, namely modified rhodamine; preferably, the stirring speed of the reflux reaction is 100 to 400 r / min; in the present invention, the substance obtained by the reflux reaction forms a stratified state after stopping stirring, the upper layer is the solvent of the reaction solution, and the lower layer is the product, for example, filtering is performed using a Buchner funnel.

[0041] According to some preferred embodiments, the epoxy resin is a bisphenol A epoxy resin, preferably, the bisphenol A epoxy resin is E51 liquid epoxy resin; and / or the mass ratio of the modified rhodamine to the epoxy resin is 1:(15-25) (for example, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or 1:25).

[0042] According to some specific implementations, step (2) is: uniformly mixing the modified rhodamine and an excess of epoxy resin in a round-bottom flask, and then treating the mixture under an argon atmosphere at 150° C. for 3 hours to obtain a rhodamine-modified epoxy resin.

[0043] According to some preferred embodiments, in step (3): the curing agent is an anhydride curing agent and / or an amine curing agent. The present invention has no special requirements for the anhydride curing agent and the amine curing agent, and those skilled in the art can select according to needs. Preferably, the anhydride curing agent is a mixture of pyromellitic anhydride and maleic anhydride (also known as maleic anhydride) in a mass ratio of (70-80): (20-30), and the amine curing agent is polyetheramine curing agent D230; and / or the mass ratio of the rhodamine-modified epoxy resin to the curing agent is 100: (20-40).

[0044] According to some preferred embodiments, the mass ratio of the first mixture to the nano alumina is 100:(20-70) (for example, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65 or 100:70).

[0045] According to some preferred embodiments, the stirring speed of the stirring treatment is 100-400 r / min; and / or the stirring treatment is performed in an air atmosphere. Unless otherwise specified, other operations of the present invention are also performed in an air atmosphere.

[0046] According to some specific implementations, step (3) is: weighing rhodamine-modified epoxy resin and curing agent in a mass ratio of 100:30, manually stirring to obtain a first mixture, and then adding nano-Al to the first mixture. 2 O 3 The filler is manually stirred until the mixture is uniform to obtain a second mixture, and then the second mixture is placed in a stirring system and stirred in an air atmosphere at 60° C. until a mechanochromic epoxy resin with a viscosity of 40,000 to 45,000 cps is obtained.

[0047] According to some preferred embodiments, the raw materials for preparing the mechanochromic epoxy resin material for the mold also include bisphenol F epoxy resin (such as Epikote 862 liquid bisphenol F epoxy resin), and the mass ratio of the mechanochromic epoxy resin to the bisphenol F epoxy resin is 10:(2-8); the mass ratio of the mechanochromic epoxy resin, the polyamide curing agent, the accelerator and the aqueous filler is 10:(3-8):(0.5-1.5):(50-80); and / or the aqueous filler includes hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water in a mass ratio of (15-25):(5-15):(5-15):(20-30); the present invention does not specifically limit the particle size of hydrophilic fumed silica, precipitated silica and nano titanium dioxide, and those skilled in the art can make conventional selections; in the present invention, the model of the hydrophilic fumed silica is, for example, HDK T30, the model of the precipitated silica is, for example, ZEODENT 103, and the model of the nano titanium dioxide is, for example, R-FC5.

[0048] According to some preferred embodiments, the polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636. Preferably, the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:(2-4); and / or the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30).

[0049] In a second aspect, the present invention provides a method for preparing the mold force-induced color-changing epoxy resin material according to the first aspect of the present invention, and a preparation flow chart, for example, as shown in Figure 1 As shown, the method comprises the following steps:

[0050] (a) mixing hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide with water to obtain an aqueous phase filler;

[0051] (b) The mechanochromic epoxy resin, the polyamide curing agent and the accelerator are mixed uniformly, and then the aqueous phase filler is added and mixed uniformly to obtain a mechanochromic epoxy resin material for a mold.

[0052] According to some preferred embodiments, in step (b), bisphenol F epoxy resin is also added.

[0053] According to some specific embodiments, the mold is prepared by using a mechanochromic epoxy resin material as follows:

[0054] (a) Preparation of aqueous phase filler: hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide are gradually added to water, and stirred at a speed of 600 r / min until all inorganic particles are evenly dispersed to form a uniform suspension, thereby obtaining an aqueous phase filler;

[0055] (b) The mechanochromic epoxy resin, bisphenol F epoxy resin, polyamide curing agent and accelerator are stirred and mixed at a rotation speed of 600 r / min to obtain a resin phase, and then a water phase filler is added to the resin phase at a rotation speed of 600 r / min and the stirring and mixing are continued to obtain a mechanochromic epoxy resin material for a mold.

[0056] The third aspect of the present invention provides the use of the mold force-chromic epoxy resin material described in the first aspect of the present invention or the mold force-chromic epoxy resin material prepared by the preparation method described in the second aspect of the present invention in the preparation of an epoxy resin mold for damage detection and / or damage warning; the purpose of the third aspect of the present invention is to provide an epoxy resin mold with a self-indicating damage function, which can provide obvious visual warnings in the early damage stage, thereby allowing timely maintenance or replacement to reduce production interruptions and improve overall safety. In addition, the promotion of this technology will help to improve the reliability of epoxy resin molds in high-risk industrial applications; when preparing the epoxy resin mold of the present invention, the mold force-chromic epoxy resin material can be placed in a molding mold designed in advance according to the epoxy resin mold structure (the inner surface of the molding mold is pre-evenly coated with a layer of release agent), and then cured at 30-40°C for 10-18h, and then demolded to obtain the epoxy resin mold.

[0057] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0058] In the following examples and comparative examples, the model of the hydrophilic fumed silica used is HDK T30, the model of the precipitated silica used is ZEODENT 103, and the model of the nano titanium dioxide used is R-FC5.

[0059] Example 1

[0060] ① In a round-bottom flask equipped with a reflux condenser, rhodamine 6G is dissolved in anhydrous ethanol, ethylenediamine is added and mixed evenly, and then refluxed for 24 hours at 80°C and 300r / min in an argon atmosphere; the obtained substance is filtered, washed three times with anhydrous ethanol, and then dried in an oven at 60°C for 3 hours to obtain modified rhodamine; wherein the mass ratio of anhydrous ethanol to rhodamine 6G is 12:1, and the molar ratio of rhodamine 6G to ethylenediamine is 1:4.

[0061] ② The modified rhodamine obtained in step ① and E51 liquid epoxy resin are mixed evenly in a round-bottom flask, and then treated at 150° C. in an argon atmosphere for 3 hours to obtain a rhodamine-modified epoxy resin; wherein the mass ratio of the modified rhodamine to the E51 liquid epoxy resin is 1:20.

[0062] ③ The rhodamine-modified epoxy resin and the anhydride curing agent obtained in step ② are weighed in a mass ratio of 100:30, and are manually stirred to obtain a first mixture, and then nano-alumina filler is added to the first mixture, and is manually stirred to obtain a second mixture, and then the second mixture is stirred in an air atmosphere at 60°C to obtain a mechanochromic epoxy resin with a viscosity of 40,000 cps; wherein the stirring speed is 300 r / min, and the anhydride curing agent is a mixture of pyromellitic anhydride and maleic anhydride in a mass ratio of 75:25; the mass ratio of the first mixture to the nano-alumina is 100:20.

[0063] ④ The hydrophilic fumed silica, precipitated silica and nano titanium dioxide were stirred and mixed at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water was 20:10:10:25; the mechanochromic epoxy resin and bisphenol F epoxy resin (EPIKOTE 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed at a mass ratio of 10:5:7:1 at a speed of 600r / min to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed at a speed of 600r / min to obtain a mechanochromic epoxy resin material for a mold; wherein the polyamide curing agent is prepared by mixing polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 at a mass ratio of 4:3; the mass ratio of mechanochromic epoxy resin, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.

[0064] Example 2

[0065] Embodiment 2 is substantially the same as Embodiment 1, except that:

[0066] ③ The rhodamine-modified epoxy resin and the amine curing agent obtained in step ② are weighed in a mass ratio of 100:30, and are manually stirred to obtain a first mixture, and then nano-alumina filler is added to the first mixture, and is manually stirred to obtain a second mixture, and then the second mixture is stirred in an air atmosphere at 60°C to obtain a mechanochromic epoxy resin with a viscosity of 37500cps; wherein the stirring speed is 300r / min, the amine curing agent is a polyetheramine curing agent D230, and the mass ratio of the first mixture to the nano-alumina is 100:20.

[0067] Comparative Example 1

[0068] The hydrophilic fumed silica, precipitated silica and nano-titanium dioxide were stirred and mixed at a speed of 600 r / min to obtain a water-phase filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano-titanium dioxide and water was 20:10:10:25; E51 liquid epoxy resin, bisphenol F epoxy resin (EPIKOTE 862 liquid bisphenol F epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed at a mass ratio of 10:5:7:1 at a speed of 600r / min to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed at a speed of 600r / min to obtain a mold force-induced color-changing epoxy resin material; wherein, the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 at a mass ratio of 4:3, and the mass ratio of E51 liquid epoxy resin, bisphenol F epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.

[0069] Comparative Example 2

[0070] Comparative Example 2 is substantially the same as Example 1, except that:

[0071] ③ Using water to stir and mix the hydrophilic fumed silica, precipitated silica and nano titanium dioxide at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water is 20:10:10:25; the rhodamine-modified epoxy resin and bisphenol F epoxy resin (EPIKOTE 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed at a mass ratio of 10:5:7:1 at a speed of 600r / min to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed at a speed of 600r / min to obtain a mold force-induced color-changing epoxy resin material; wherein, the polyamide curing agent is mixed by polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 at a mass ratio of 4:3; the mass ratio of rhodamine modified epoxy resin, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.

[0072] Comparative Example 3

[0073] Comparative Example 3 is substantially the same as Example 1, except that:

[0074] ③ The rhodamine-modified epoxy resin and the anhydride curing agent obtained in step ② are weighed in a mass ratio of 100:30, and manually stirred to obtain a first mixture, and then nano-alumina filler is added to the first mixture, and manually stirred to obtain a second mixture, which is used as a mechanochromic epoxy resin; wherein the anhydride curing agent is a mixture of pyromellitic anhydride and maleic anhydride in a mass ratio of 75:25; the mass ratio of the first mixture to the nano-alumina is 100:20.

[0075] Comparative Example 4

[0076] ① E51 liquid epoxy resin and rhodamine 6G were weighed in a mass ratio of 100:5, and manually stirred to obtain a first mixture. Nano-alumina filler was added to the first mixture, and manually stirred to obtain a second mixture, which was a modified epoxy resin; wherein the mass ratio of the first mixture to the nano-alumina was 100:20.

[0077] ② The hydrophilic fumed silica, precipitated silica and nano titanium dioxide were stirred and mixed uniformly at a speed of 600 r / min with water to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water was 20:10:10:25; the modified epoxy resin obtained in step ①, bisphenol F epoxy resin (EPIKOTE862 liquid bisphenol F epoxy resin), polyamide curing agent and accelerator DMP-30 were stirred and mixed uniformly at a speed of 600 r / min ... mass ratio of 10:5:7:1. r / min and stir and mix evenly to obtain a resin phase, add a water phase filler to the resin phase at a rotation speed of 600 r / min and continue to stir and mix evenly at a rotation speed of 600 r / min to obtain an epoxy resin material; wherein the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:3, and the mass ratio of modified epoxy resin, bisphenol F epoxy resin, polyamide curing agent, accelerator DMP-30 and water phase filler is 10:5:7:1:65.

[0078] In order to evaluate the performance of the mold-induced color-changing epoxy resin material, the mold-induced color-changing epoxy resin material prepared in each embodiment and each comparative example was cured at 35°C for 12 hours to obtain a mold-induced color-changing epoxy resin material cured sample, and then the bending strength, Shore hardness, and the pressure threshold for slight color change under natural light and the pressure threshold for slight fluorescent color change under 365nm ultraviolet light were measured, as shown in Table 1. The present invention also provides a fluorescence spectrum curve of the mold-induced color-changing epoxy resin material cured sample obtained in Example 1 before and after compression deformation under a pressure of 20MPa, as shown in Table 1. Figure 2 shown; from Figure 2 It can be seen from the results that the broad peak at 380-500nm before and after compression deformation is the peak caused by the autofluorescence of the rhodamine-modified epoxy resin. After compression deformation, a relatively sharp peak appears at 550-607nm, which is obviously different from the peak caused by the autofluorescence of the rhodamine-modified epoxy resin at 380-500nm, indicating that the sample after compression deformation has been subjected to force discoloration and the fluorescence response has been turned on. This shows that the mold force-induced color-changing epoxy resin composite material prepared by the present invention has the characteristics of force-induced color change.

[0079] Table 1

[0080]

[0081]

[0082] In Table 1, the symbol “-” indicates that the performance indicator does not exist.

[0083] From the results in Table 1, it can be seen that the samples of Examples 1 to 2 filled with nano-alumina of the present invention show more obvious color development under natural light and fluorescent color change under 365nm ultraviolet light than the sample of Comparative Example 2 filled with no nano-alumina; the pressure threshold for producing slight color change under natural light and the pressure threshold for producing slight fluorescent color change under ultraviolet light of the sample of Comparative Example 2 filled with no nano-alumina are significantly higher, and the early warning for microscopic damage is insufficient; while the pressure threshold for producing slight color change under natural light and the pressure threshold for producing slight fluorescence under ultraviolet light of the samples of Examples 1 to 2 filled with nano-alumina are significantly lower, and can provide accurate and sufficient early warning.

[0084] It can be seen from the data in Table 1 that the bending strength of the mold-induced chromic epoxy resin material prepared in the embodiment of the present invention is as high as 14.5 MPa or more, indicating that it has good structural integrity and bending resistance when subjected to external pressure, and that the mold-induced chromic epoxy resin material has high toughness and a hardness of more than 68D, indicating that the material has the hardness and wear resistance of a ceramic mold and is suitable for manufacturing a ceramic mold for bearing a large mechanical load.

[0085] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A mold-induced color-changing epoxy resin material, characterized in that: The mechanochromic epoxy resin material for the mold comprises a mechanochromic epoxy resin, a polyamide curing agent, an accelerator and an aqueous filler; the aqueous filler comprises hydrophilic fumed silica, precipitated white carbon black, nano titanium dioxide and water in a mass ratio of (15-25): (5-15): (5-15): (20-30); The preparation of the mechanochromic epoxy resin comprises the following steps: (1) mixing rhodamine 6G and ethylenediamine uniformly with anhydrous ethanol and subjecting the mixture to a reflux reaction, followed by filtering, washing and drying to obtain modified rhodamine; (2) uniformly mixing the modified rhodamine and the epoxy resin and treating at 130 to 180° C. for 2 to 4 hours to obtain a rhodamine-modified epoxy resin; (3) The rhodamine-modified epoxy resin and the curing agent are mixed uniformly to obtain a first mixture, and then nano-alumina is added to the first mixture and mixed uniformly to obtain a second mixture, and then the second mixture is stirred at 60 to 100° C. to obtain a mechanochromic epoxy resin with a viscosity of 40,000 to 45,000 cps.

2. The mold-use mechanochromic epoxy resin material according to claim 1, characterized in that: The molar ratio of the rhodamine 6G to the ethylenediamine is 1:(3.5-4.5); The mass ratio of the anhydrous ethanol to the rhodamine 6G is (10-15):1; and / or The temperature of the reflux reaction is 70-90° C., and the time of the reflux reaction is 18-30 hours.

3. The mold-use mechanochromic epoxy resin material according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin; and / or The mass ratio of the modified rhodamine to the epoxy resin is 1:(15-25).

4. The mold-use mechanochromic epoxy resin material according to claim 1, characterized in that: In step (3): The curing agent is an anhydride curing agent and / or an amine curing agent; The mass ratio of the rhodamine modified epoxy resin to the curing agent is 100:(20-40); and / or The mass ratio of the first mixed material to the nano-alumina is 100:(20-70).

5. The mold-use mechanochromic epoxy resin material according to claim 1, characterized in that: The stirring speed of the stirring process is 100 to 400 r / min.

6. The mold-use mechanochromic epoxy resin material according to any one of claims 1 to 5, characterized in that: The mechanochromic epoxy resin material for the mold further comprises bisphenol F epoxy resin, and the mass ratio of the mechanochromic epoxy resin to the bisphenol F epoxy resin is 10:(2-8); The mass ratio of the mechanochromic epoxy resin, the polyamide curing agent, the accelerator and the aqueous phase filler is 10:(3-8):(0.5-1.5):(50-80).

7. The mold-use mechanochromic epoxy resin material according to any one of claims 1 to 5, characterized in that: The polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636; and / or The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

8. The method for preparing the mechanochromic epoxy resin material for molds according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (a) mixing hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide with water to obtain an aqueous phase filler; (b) The mechanochromic epoxy resin, the polyamide curing agent and the accelerator are mixed uniformly, and then the aqueous phase filler is added and mixed uniformly to obtain a mechanochromic epoxy resin material for a mold.

9. The preparation method according to claim 8, characterized in that: In step (b), bisphenol F type epoxy resin is also added.

10. Use of the mold-forming mechanochromic epoxy resin material according to any one of claims 1 to 7 or the mold-forming mechanochromic epoxy resin material prepared by the preparation method according to claim 8 or 9 in preparing epoxy resin molds for damage detection and / or damage warning.

Citation Information

Patent Citations

  • Regulation and control method for force-induced discoloration wave band of aromatic disulfide epoxy

    CN114989563A

  • Mechanochromic polyester polyol as well as preparation method and application thereof

    CN117004001A